2019
DOI: 10.1155/2019/8132547
|View full text |Cite
|
Sign up to set email alerts
|

A Hyperchaotic Color Image Encryption Algorithm and Security Analysis

Abstract: The current common color image encryption algorithms applying “scrambling-diffusion” have some problems, such as the small key space, the cumbersome encryption process, and the security vulnerability. Aiming at these problems, this paper proposes a new color image encryption algorithm based on the hyperchaotic system and applying “transforming-scrambling-diffusion” model. Before scrambling, in accordance with the plaintext itself attributes, the number of iterations was calculated, all the pixel values of colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…e security of a block cipher mainly depends on the strength of the encryption algorithm and the secrecy of the secret key. e security of an encryption algorithm is achieved through the nonlinear and linear functions/components [1]. Substitution box(s) or some multiplication functions are used to introduce the nonlinearity in the encryption algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…e security of a block cipher mainly depends on the strength of the encryption algorithm and the secrecy of the secret key. e security of an encryption algorithm is achieved through the nonlinear and linear functions/components [1]. Substitution box(s) or some multiplication functions are used to introduce the nonlinearity in the encryption algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…We can observe in the proposed algorithm the sensitivity of the generated secret key x by 12 10 − , or any value of 1 r and 2 r by 1.…”
Section: Key Sensitivity Analysismentioning
confidence: 99%
“…Later, in 2017, Shaikh, Chapaneri et al [11] proposed a color image encryption algorithm, which is a single round-based hyperchaotic system due to bi-directional pixel diffusion that contributes towards an increased security and improved efficiency. Recently, in 2019, Chenghai Li et al used the "transforming-scrambling-diffusion" model to introduce a hyperchaotic color image encryption algorithm that depends on converting the pixel values into gray codes before scrambling [12]. In the same year, Priya Ramasamy et al suggested an improved logistical map while using a chaotic maps function and uncomplicated encryption techniques, such as block scrambling and modified zigzag transformation, for encryption phases [13].…”
Section: Introductionmentioning
confidence: 99%
“…By using a single round based hyper-chaotic system, Shaikh et al presented a color image encryption method with bi-directional pixel diffusion [ 15 ]. Additionally, Li et al presented a "transforming-scrambling-diffusion” model based color image encryption method with a four-dimensional (4D) hyper-chaotic system, which could convert pixel values to gray format before scrambling [ 16 ]. There is no doubt that some of the encryption methods in these chaos-based schemes still have weaknesses to some extent.…”
Section: Introductionmentioning
confidence: 99%